1993
DOI: 10.1159/000462384
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Red-Cell Glycolipid Patterns of Le(a+b+) and Le(a+b-) Polynesians as Further Evidence of the Weak Secretor Gene Se^w

Abstract: Monoclonal antibodies and thin-layer chromatography were used to study the unusual erythrocyte Lewis phenotypes found in healthy Polynesians. A single monoclonal anti-Le^b reagent 073 (clone LM129) was found which could detect Le^b antigen on the Polynesian erythrocytes of samples that were unreactive with various polyclonal and monoclonal anti-Le^b reagents. Glycolipid fractions prepared from the plasma and erythrocytes of selected Polynesian samples of red-cell Le(a-b-), Le(a+b-) and Le(a+b+) phenotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 13 publications
7
25
0
Order By: Relevance
“…accumulating over the years to suggest that the Lewis and secretor systems at the phenotypic level in some popula tions, particular Polynesians [7], are more complex than first thought. Further complexities are seen with the differ ential expression of Lewis antigens in different tissues [8,9] and a-4-fucosyltransferase activity in epithelial tissues of red-cell Lewis-negative individuals [10].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…accumulating over the years to suggest that the Lewis and secretor systems at the phenotypic level in some popula tions, particular Polynesians [7], are more complex than first thought. Further complexities are seen with the differ ential expression of Lewis antigens in different tissues [8,9] and a-4-fucosyltransferase activity in epithelial tissues of red-cell Lewis-negative individuals [10].…”
Section: Methodsmentioning
confidence: 99%
“…In order to further study the formation of LeJ and Leb antigens and to study the extended Lewis structures found in the plasma of Polynesians [7] we undertook an extensive evaluation of the Lewis glycolipids in Lewis-negative indi viduals. Nonacid glycolipids were prepared from plasma of Lewis-negative Caucasian and Polynesian individuals of nonsecretor and secretor phenotypes, and one sample of the Polynesian partial-secretor phenotype [5,7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations